2007
DOI: 10.1002/bem.20316
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic‐field‐induced vertigo: A theoretical and experimental investigation

Abstract: Vertigo-like sensations or apparent perception of movement are reported by some subjects and operators in and around high field whole body magnetic resonance body scanners. Induced currents (which modulate the firing rate of the vestibular hair cell), magneto-hydrodynamics (MDH), and tissue magnetic susceptibility differences have all been proposed as possible mechanisms for this effect. In this article, we examine the theory underlying each of these mechanisms and explore resulting predictions. Experimental e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
209
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(225 citation statements)
references
References 31 publications
(30 reference statements)
9
209
1
4
Order By: Relevance
“…A recent study (37) assessed possible underlying mechanisms of induced vertigo-like sensations under well controlled exposure conditions, but in relatively small populations (N ϭ 12, 10, and 10). The researchers concluded that, in agreement with theoretical predictions, induced vertigo results from magnetic susceptibility differences between vestibular tissue and fluids, as well as induced currents, which present the brain with confusing information.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (37) assessed possible underlying mechanisms of induced vertigo-like sensations under well controlled exposure conditions, but in relatively small populations (N ϭ 12, 10, and 10). The researchers concluded that, in agreement with theoretical predictions, induced vertigo results from magnetic susceptibility differences between vestibular tissue and fluids, as well as induced currents, which present the brain with confusing information.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no similar descriptions in previous studies, although right head tilt was reported in rats at 14.1 T, 20 and a sensation of falling forward or backward was reported in humans at 7T. 11 The mechanisms of this phenomenon are unknown, but it can be caused by stimulation of the vestibulocochlear nerve or inner ear organs during gradual changes in magnetic field strength at a slow table speed.…”
Section: Discussionmentioning
confidence: 78%
“…This can be measured by monitoring their postural sway whilst they fix their gaze on a spot whilst opening and closing their eyes. Subjects report a sudden onset of the effect near the magnet as would be expected with an effect related to the square of the magnetic field [9].…”
Section: Susceptibility-induced Forcesmentioning
confidence: 87%
“…In the light of the physics of magnetic field interactions, it is now possible to discuss four likely candidates for the sensation of MFIV which have their origins in the vestibular system: forces due to the susceptibility of vestibular structures; current flow due to a net rate of change of magnetic flux; MHD due to head movement [8,9] and fluid pressure due to Lorentz forces [10].…”
Section: Magnetic Field Induced Vertigomentioning
confidence: 99%
See 1 more Smart Citation